Parental conflicts and resource sharing: Evolutionary trade-off - Ruby Dhar; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences)
The genetic struggle between parents and their offspring is a fundamental aspect of kin selection theory and the gene-centered perspective of evolution. Parental resource conflict, or parent-offspring conflict, is an intriguing concept within evolutionary biology. It refers to the natural disagreement between parents and their young regarding how parental resources should be distributed. This disagreement emerges from the differing evolutionary goals of parents for their offspring.